2007
DOI: 10.1038/sj.cgt.7701042
|View full text |Cite
|
Sign up to set email alerts
|

CCL19 (ELC) as an adjuvant for DNA vaccination: induction of a TH1-type T-cell response and enhancement of antitumor immunity

Abstract: Coexpression of tumor antigens together with immunomodulatory molecules is a strategy in DNA vaccination aiming at an amplification of the antitumor immune response. Epstein-Barr virus-induced-molecule-1-ligand-chemokine (ELC/CCL19) is a CC chemokine that binds to the chemokine receptor CCR7. CCR7 is expressed on mature dendritic cells (DC) and distinct T-and B-cell subpopulations. CCL19 (ELC) is mainly expressed in secondary lymphoid organs and plays a central role in regulating the encounters between DC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…Previously, we reported that PBMCs from RRP patients respond to HPV proteins with increased expression of T H 2-like and regulatory cytokines without adequate expression of IFN-γ (8 to influenza virus (17). Additionally, CCL19 and CCL21 have been used as adjuvants to enhance CTL responses to tumors (20). Consistent with this, papillomas do not contain significant numbers of CTLs (9).…”
Section: Discussionsupporting
confidence: 60%
“…Previously, we reported that PBMCs from RRP patients respond to HPV proteins with increased expression of T H 2-like and regulatory cytokines without adequate expression of IFN-γ (8 to influenza virus (17). Additionally, CCL19 and CCL21 have been used as adjuvants to enhance CTL responses to tumors (20). Consistent with this, papillomas do not contain significant numbers of CTLs (9).…”
Section: Discussionsupporting
confidence: 60%
“…CCL19 can directly affect immune responses of T cells and dendritic cells by skewing them towards a proinflammatory (Th1) response 48 49. However, CCL19 may have roles that depend on the species, as many of the CCL19 effects on Th1 skewing have been found in mice, some studies using CCL19/CCL21-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…CCR7 is also expressed on activated B cells and DCs, increasing the chance of interactions between DCs, T cells, and B cells in secondary lymphatic tissue. Previous studies demonstrated that CCL19 promotes antitumor activity (44,45) and enhances protective immune responses against HSV-1 (40).…”
mentioning
confidence: 99%